The Urgency of Expanding Victim Assistance Funds for Child Victims of Crime - Arthur Hulu, Samuel; Kholiq, Abdul (Law Development Journal, 2025)
A child who is a victim of a criminal offense needs both material and immaterial recovery. Unfortunately, to date, both restitution and compensation have not been able to provide material reparation to child victims of crime. Both mechanisms are considered to have weaknesses that hinder the fulfillment of material rights for victims in order to restore their condition. The implementation of victim assistance funds as a mechanism that functions if the confiscated assets of the convicted person are not sufficient to fulfill the value of restitution. Currently, victim assistance funds can only be applied to victims of sexual violence crimes. However, currently the victim assistance fund cannot be utilized by all children who are victims of any criminal offense. Therefore, this research will discuss in depth the urgency of expanding victim assistance funds for child victims of criminal acts.